Поэтика и контекст оды Михаила Кузмина «Враждебное море» (1917) [“Vrazhdebnoe more” (“The Hostile Sea,” 1917) by Mikhail Kuzmin: The Ode’s Poetics and Context] - Pakhomova, Alexandra (Slavica Revalensia, 2020)
The article explores Mikhail Kuzmin’s poem The Hostile Sea (Vrazhdebnoe More) in the context of the poet’s attitude to the First World War and the Russian Revolution. It brings into focus the poem’s main images and themes in their relation to the revolutionary rhetoric and Kuzmin’s poetic system. Particular attention is paid to the dialogue between Kuzmin and Vladimir Mayakovsky as reflected in this poem. In addition, the article traces the history of the poem from its creation in 1917 to the poem’s first publication in 1918.